Teknik Relaksasi Napas Dalam dengan Kombinasi Dzikir Asmaul Husna terhadap Tekanan Darah pada Pasien Hipertensi - Dimas Utomo Hanggoro Putro; Wati Jumaiyah; Masmun Zuryati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of deep breathing relaxation therapy with a combination of Asmaul Husna dhikr on reducing blood pressure in hypertensive patients. The research design used a quasi-experimental design with a pre-test and post-test control group design. The results of the study found that in the treatment group the blood pressure before the 1st day of intervention was 140/90 mmHg. Meanwhile, the median blood pressure before the 2nd day of intervention was 145/90 mmHg. Systolic blood pressure after being given the 10-minute treatment group intervention found that the median blood pressure after the 1st day of intervention was 130/80 mmHg. Meanwhile, the median blood pressure after the 2nd day of intervention was 135/80 mmHg. The results of the analysis of the treatment group obtained a p-value <0.05 and in the control group >0.05. In conclusion, there is an effect of deep breathing relaxation techniques with a combination of Asmaul Husna dhikr on reducing blood pressure. Keywords: Asmaul Husna Dhikr, Hypertension, Deep Breathing Relaxation, Blood Pressure